Peramalan Inflasi Menurut Kelompok Pengeluaran Makanan Jadi, Minuman, Rokok dan Tembakau Menggunakan Model Variasi Kalender (Studi Kasus Inflasi Kota Semarang) - Berlian, Amanda Lucky; Wilandari, Yuciana; Yasin, Hasbi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Inflation is rising prices in general and continuously. Inflationary expenditure groups are divided into seven groups, and one group which spending considerable influence current inflation in Indonesia is by expenditure groups, food, beverages, cigarettes and tobacco. This is because the Indonesian people are very consumptive, especially when it coming to Eid. The movement of the month when Eid occurs once in every three years, so that changes raises a calendar variation. Calendar variation method is a method which modifies the dummy regression models with ARIMA models. In this final project, modeling and forecasting of inflation data by type of expenditure, food, beverages, cigarettes and tobacco in Semarang using variations of the calendar with holidays variation effects due to Eid. Based on the analysis and discussion shows that the best calendar variation model is ARIMA (1,0,0), with the forecasting results shows a significant increase of inflation when the month of Ramadan come.Keywords : inflation, calendar variation, the dummy regression, ARIMA